Descemet Stripping Only for a Chronic Descemet Detachment After Cataract Surgery. Issue 3 (March 2020) - Hirabayashi, Kristin E.; Mark, David; Lau, Jackson; Lin, Charles C.
Abstract : Purpose: To describe a case of postsurgical corneal decompensation in a patient with Fuchs endothelial dystrophy with a sectoral Descemet detachment and corneal edema that was successfully managed with a targeted Descemet stripping only (DSO) procedure. Methods: This is a case report and review of the literature. Results: A female patient with Fuchs endothelial dystrophy presented with a 6-month history of a persistent sectoral Descemet membrane detachment after cataract surgery with overlying corneal edema. Specular microscopy demonstrated moderate cell dropout with a cell density of 929 cells/mm 2 in the affected eye. Intracameral air injection was attempted without improvement, and a sectoral DSO procedure was performed. Netarsudil and prednisolone were used postoperatively, and she demonstrated gradual improvement with resolution of the edema by postoperative week 10 and a central endothelial cell density of 675 cells/mm 2 by postoperative month 8. Conclusions: DSO is a viable therapy in certain cases of postsurgical corneal decompensation.